A case of premenopausal breast cancer with symptomatic cerebellar metastasis successfully treated by systemic endocrine therapy alone: relationship to biological features - Fujiki, Yoshitaka (Int Cancer Conf J, 2016)
We report a case of premenopausal breast cancer with symptomatic cerebellar metastasis successfully treated by systemic endocrine therapy alone. The patient developed dysarthria, headache, lightheadedness and became difficult to write gradually. The cerebellar tumor was detected by computed tomography (CT) and was suspected hemangioma or hemangioblastoma. The tumor was resected and histologically diagnosed as poorly differentiated adenocarcinoma or squamous cell carcinoma. A whole body CT scan revealed a right thyroid tumor and left breast tumor. Core needle biopsy of the breast tumor histologically diagnosed the tumor as estrogen receptor positive, progesterone receptor positive, human epidermal growth factor receptor-2 negative, and Ki-67 labeling index 5%. After these examinations, histologically, the resected cerebellar tumor showed the same subtype as the breast tumor, so the final diagnosis was metastatic breast cancer with cerebellar metastasis. The patient subsequently received radiotherapy with the CyberKnife and endocrine therapy without resection of the thyroid tumor. Her medical condition has maintained a good response and stable disease for 7.5 years after the start of treatment. Analysis of four ESR1 mutations showed no mutations in the cerebellar metastatic lesion and breast cancer tissue. Our findings show that these tumors have high hormone responsiveness.